2021
DOI: 10.1186/s12879-021-05793-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course and challenging management of early COVID-19 infection after heart transplantation: case report of two patients

Abstract: Background There are limited data on Coronavirus disease 2019 (COVID-19) in solid organ transplant patients, especially in heart transplant recipients, with only a few case reports and case series described so far. Heart transplant recipients may be at particular high risk due to their comorbidities and immunosuppressed state. Case presentation This report describes the clinical course and the challenging management of early COVID-19 infection in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Five databases were used to find 2818 articles related to COVID-19 infection in HT and heart-kidney transplant recipients. Thirty-three studies were then deemed eligible for inclusion in this review [ 7 39 ]. A PRISMA flow diagram detailing the process of identification, inclusion, and exclusion of studies is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five databases were used to find 2818 articles related to COVID-19 infection in HT and heart-kidney transplant recipients. Thirty-three studies were then deemed eligible for inclusion in this review [ 7 39 ]. A PRISMA flow diagram detailing the process of identification, inclusion, and exclusion of studies is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Of the thirty-three studies, eleven were retrospective case series [ 7 , 11 , 14 , 19 , 20 , 26 , 29 33 , 38 , 39 ], while twenty-two were case reports [ 8 – 10 , 12 , 13 , 15 18 , 21 25 , 27 , 28 , 34 – 37 ]. All were peer-reviewed.…”
Section: Resultsmentioning
confidence: 99%
“…While the literature for adult patients with heart transplants is limited to case reports and small case series, there is some suggestion that infection early after transplant may have an impact on outcomes ( 20 , 21 , 22 ). A US cohort of 28 adult heart transplant patients reported a 25% case fatality rate ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, one-fifth of the patients were <1 year post transplant with one death in this group. This is an important group of patients to continue to monitor, given the reports of adults experiencing worse outcomes in the early phase post HTx ( 20 , 21 , 22 ) Whether reduction in immunosuppression is warranted in this specific group of patients is unclear.…”
Section: Discussionmentioning
confidence: 99%
“… [28] Lima et al, showed negative impact of COVID-19 in five heart transplants. [29] Tchana-Sato et al reported two fatalities in perioperative COVID-19 heart transplantation with COVID-19 [30] Keller et al detailed a deceased donor lung transplant who acquired early covid-19 required mechanical ventilation. [31] Dale et al described two cases of early liver transplant who contracted severe COVID-19 and recovered.…”
Section: Discussionmentioning
confidence: 99%